Pendampingan Pelestari Anggrek melalui Program Adopsi dan Pengembalian Vanda tricolor di Lereng Gunung Merapi - Rineksane, Innaka Ageng; Astuti, Agung; Samidjo, Gatot Supangkat; Wulandari, Rani Agustina; Putri, Adinda Anisa (Unri Conference Series: Community Engagement, 2024)
The Merapi orchid conservation farmer group is in Turgo, Purwobinangun, Sleman, Yogyakarta. This agricultural collective preserves the Merapi orchid and reintroduces it to its native environment on the slopes of Mount Merapi. Vanda tricolor is an orchid species that requires conservation owing to its declining population, attributed to recurrent eruptions and the exploitation of its native habitat. This adoption initiative necessitates expertise and financial resources; thus, support for farmer groups is essential. The proposed method involves counseling and support for farmers. This program aims to enhance the knowledge and skills of farmer group members and orchid conservation advocates in the adoption and reintroduction of Vanda tricolor orchids to their native habitat. This service is implemented by counseling, facilitating equipment and technology transfer, aiding in adopting and returning orchids, and conducting monitoring and evaluation. The event was attended by 5 men and 8 women, all members of the farmer group and supporters of orchid conservation in Merapi. Three adult Vanda tricolor specimens have been reattached to the puspa tree on the slopes of Mount Merapi. The pre-and post-test analysis results indicated that participants' knowledge and comprehension of the adoption and return of Merapi orchids improved from 27.9% to 100% following direct explanations and practical experience.